The mask and the message: musical figuring of Lagbaja's artful diplomacy (2015)
The conceptual adoption of a hidden personality by Lagbaja, Nigeria's famous masked popular music artiste, to depict the facelessness of the common man represents artful diplomacy within African cultural milieu. Lagbaja relies on various resource materials including Yoruba folklore, oriki (descriptive poetry), owe (proverbs), afojuinuwo (imagination) and ohun to nlo (current affairs) in his satirical compositions. Through these elements, the artiste succeeds in making graphical representations of figures to facilitate transformative visualisation of the various political and socio-economic occurrences in Nigeria without attracting any negative consequences on his person. This paper adopts Louise Meintjes' concept of music figure to analyse how Lagbaja deploys definitive narratives in negotiating his crusade for an egalitarian society. Specific attention is drawn to the nuance with which the artiste critiques the double burden state of Nigeria's polity as represented by her leaders' repressive actions on one hand, and corollary inactions of and consequences on the led on the other. The paper posits that the figuring of the dynamics of events that shape the day-to-day ordinary life of Nigerians facilitates its proper contextualisation in the reading and interpretation of Lagbaja's songs and drum texts.